Spectra of spontaneous frameshift mutations at the hisD3052 allele of Salmonella typhimurium in four DNA repair backgrounds. - DeMarini, D M (1998)
To characterize the hisD3052 -1 frameshift allele of Salmonella typhimurium, we analyzed approximately 6000 spontaneous revertants (rev) for a 2-base deletion hotspot within the sequence (CG)4, and we sequenced approximately 500 nonhotspot rev. The reversion target is a minimum of 76 bases (nucleotides 843-918) that code for amino acids within a nonconserved region of the histidinol dehydrogenase protein. Only 0.4-3.9% were true rev. Of the following classes, 182 unique second-site mutations were identified: hotspot, complex frameshifts requiring DeltauvrB + pKM101 (TA98-specific) or not (concerted), 1-base insertions, duplications, and nonhotspot deletions. The percentages of hotspot mutations were 13.8% in TA1978 (wild type), 24.5% in UTH8413 (pKM101), 31.6% in TA1538 (DeltauvrB), and 41.0% in TA98 (DeltauvrB, pKM101). The DeltauvrB allele decreased by three times the mutant frequency (MF, rev/10(8) survivors) of duplications and increased by about two times the MF of deletions. Separately, the DeltauvrB allele or pKM101 plasmid increased by two to three times the MF of hotspot mutations; combined, they increased this MF by five times. The percentage of 1-base insertions was not influenced by either DeltauvrB or pKM101. Hotspot deletions and TA98-specific complex frameshifts are inducible by some mutagens; concerted complex frameshifts and 1-base insertions are not; and there is little evidence for mutagen-induced duplications and nonhotspot deletions. Except for the base substitutions in TA98-specific complex frameshifts, all spontaneous mutations of the hisD3052 allele are likely templated. The mechanisms may involve (1) the potential of direct and inverted repeats to undergo slippage and misalignment and to form quasi-palindromes and (2) the interaction of these sequences with DNA replication and repair proteins.